Hubungan Paritas dan Dukungan Keluarga dengan Mual Muntah pada Ibu Hamil Trimester I di Puskesmas Arga Indah 2 Bengkulu Tengah Tahun 2025 - Ermakris Adelina; Ronalen Br. Situmorang; Ice Rakizah Syafrie (Utami Publisher, 2026)
According to data from the World Health Organization (WHO) in 2018 the incidence of nausea and vomiting was 124.348 pregnant women (21.5%) generally at 8 weeks of pregnancy. In 2019 it increased more sharply to around 137.731 pregnant women, in 2020 it was 142.488 pregnant women (22.9%), in 2021 it was 148.435 pregnant women and in 2022 it was 152.376 pregnant women, from the data above there were fluctuating incidence rates of nausea and vomiting over 5 years (Ika Rahmi, 2023). The purpose of this study was to determine the relationship between parity and family support with nausea and vomiting in pregnant women in the first trimester at Arga Indah 2 Health Center, Central Bengkulu in 2025. The research method used quantitative with a sample size of 46 pregnant women. The data analysis of this study used the Chi Square statistical test (α=0.05). The results of the study showed that the majority of respondents, namely 31 (67.4%) respondents had primiparous parity. Some respondents, namely 28 (60.9%) respondents had family support that was supportive. The chi square test results found that there is a relationship between parity and family support with nausea and vomiting in pregnant women in the first trimester at Arga Indah 2 Health Center, Central Bengkulu in 2025 with p=0.000 which means p <0,05. Namely H1 accepted. The conlusion of this study is that is a relationship between party and family support with nausea and vomiting in pregnen women in the first trimester at arga indah 2 health center, central Bengkulu. Conseling need to be carried out for pregnen women at BPM, health center, hospital and health service locations to improve the health of pregnenat wome n by reducing the nausea and vomiting experienced by prengan women and routinely undergoing healty pregnancy examination.